Outcome of COVID-19 in Patients With Mantle Cell Lymphoma—Report From the European MCL Registry. Issue 5 (8th May 2022) - Tilch, Marie-Kristin; Visco, Carlo; Kinda, Sandra; Hermine, Olivier; Kohn, Milena; Besson, Caroline; Lamure, Sylvain; Duléry, Rémy; Ragaini, Simone; Eyre, Toby A.; Van Meerten, Tom; Ohler, Anke; et al.
Abstract : Data on outcome of patients with mantle cell lymphoma (MCL) and COVID-19 infection are limited. The European MCL (EMCL) registry is a centralized registry of the EMCL network, collecting real-world information about treatments and disease courses. During the COVID-19 pandemic, additional data on MCL patients with COVID-19 infection were collected, aiming to identify risk factors for mortality from COVID-19. In our retrospective, multicenter, international study, we collected data from 63 MCL patients with a median age of 64 years (range, 44–84) in 9 countries with evidence of a COVID-19 infection between February 2020 and October 2021. The overall mortality rate was high (44.4%), especially in hospitalized patients (61%) and in patients with need for intensive care unit care (94%). Patients receiving rituximab had significantly poorer survival than patients not receiving rituximab ( P = 0.04). Our data highlight the importance of prevention strategies and underline the need for effective vaccination in this vulnerable cohort.